2020
DOI: 10.3389/fmicb.2020.00694
|View full text |Cite
|
Sign up to set email alerts
|

Weaning Alters Intestinal Gene Expression Involved in Nutrient Metabolism by Shaping Gut Microbiota in Pigs

Abstract: Weaning transition usually impairs intestinal architecture and functions and results in gut-associated disorders in pigs. Understanding the changes in intestinal transcriptome and gut microbiota during weaning transition is important for elucidating the underlying mechanism of weaning stress. In the present study, we performed RNA-seq to determine the changes in intestinal transcriptome and 16S rRNA sequencing to measure the gut microbiota changes in the weaning transition. Transcriptome results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 71 publications
1
33
0
Order By: Relevance
“…On the genus level, it is well documented that Bacteroides are known to provide an advantage in the use of milk oligosaccharides as carbon sources [33]. Similar with other studies, the abundance of Bacteroides was higher before weaning in both groups [14,15]. However, the abundance of Bacteroides in the SC group was signi cantly lower than that in the CON group, which might suggest that the early social contact might help the piglets communicate more and eat more of the solid food that we supplied, as both groups of piglets could freely access solid food from 20 days of age.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…On the genus level, it is well documented that Bacteroides are known to provide an advantage in the use of milk oligosaccharides as carbon sources [33]. Similar with other studies, the abundance of Bacteroides was higher before weaning in both groups [14,15]. However, the abundance of Bacteroides in the SC group was signi cantly lower than that in the CON group, which might suggest that the early social contact might help the piglets communicate more and eat more of the solid food that we supplied, as both groups of piglets could freely access solid food from 20 days of age.…”
Section: Discussionsupporting
confidence: 86%
“…Weaning transition is an important development stage in pigs as it impacts the intestinal microbial structure and function [14,15]. Under modern intensive farming practices, farmers pursue economic bene ts by weaning piglets at a very early age, which obviously causes stress that depresses piglet food intake, growth, immune response, oxidative stress and neuroendocrine function [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the faecal bacterial composition of swine varies significantly in different growth stages ( Kim et al., 2015b ). Being one of the important landmarks of the production stage, the weaning transition was found to significantly alter the swine gut microbiota composition and the pathways concerning nutrient metabolism ( Meng et al., 2020 ).…”
Section: Swine Gut Microbiota and Their Influencing Factorsmentioning
confidence: 99%
“…Many studies have indicated that the weaning transition activates inflammation and stress signaling pathways and leads to abnormal expression of intestinal genes and proteins in pigs ( Wang et al, 2008 ; Hu et al, 2013 ). Meng et al (2020) performed RNA-seq to determine the changes in the intestinal transcriptome and conducted 16S rRNA sequencing to measure the gut microbiota changes during the weaning transition. They found that the weaning transition altered the intestinal expression of genes involved in nutrient absorption, transportation, and metabolic processes and significantly decreased the abundances of Proteobacteria and Fusobacteria in piglets.…”
Section: Introductionmentioning
confidence: 99%